2014
DOI: 10.1590/s0036-46652014000100006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro ANTIGIARDIAL ACTIVITY OF THE CYSTEINE PROTEASE INHIBITOR E-64

Abstract: The quest for new antiparasitic alternatives has led researchers to base their studies on insights into biology, host-parasite interactions and pathogenesis. In this context, proteases and their inhibitors are focused, respectively, as druggable targets and new therapy alternatives. Herein, we proposed to evaluate the in vitro effect of the cysteine protease inhibitor E-64 on Giardia trophozoites growth, adherence and viability. Trophozoites (105) were exposed to E-64 at different final concentrations, for 24,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…To test whether diltiazem inhibits SARS-CoV-2 infection at a late stage in Vero-E6 cells, we added diltiazem/E64D at 6 h post-infection, and determined the viral titer at 24 h post-infection. E64D inhibits cathepsin L [ 35 ] and prevents the infection of progeny viruses. The results showed that the viral titer in diltiazem-treated Vero-E6 cells was comparable to that of control cells, indicating that diltiazem has no effect on SARS-CoV-2 infection at a late stage ( Fig 2F ).…”
Section: Resultsmentioning
confidence: 99%
“…To test whether diltiazem inhibits SARS-CoV-2 infection at a late stage in Vero-E6 cells, we added diltiazem/E64D at 6 h post-infection, and determined the viral titer at 24 h post-infection. E64D inhibits cathepsin L [ 35 ] and prevents the infection of progeny viruses. The results showed that the viral titer in diltiazem-treated Vero-E6 cells was comparable to that of control cells, indicating that diltiazem has no effect on SARS-CoV-2 infection at a late stage ( Fig 2F ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our experiments used inhibitors, which have previously been shown to successfully attenuate catB and L cysteine proteases in mammalian and protozoan parasites [ 24 , 52 , 55 , 73 ], including G . duodenalis [ 34 , 67 ]. Results from this study corroborate previous observations that G .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that concentrations of 10μM E-64d or Ca-074Me do not affect G . duodenalis trophozoite viability, but significantly reduce cathepsin-like cysteine protease activity [ 34 , 67 ]. Therefore, experiments involving G .…”
Section: Methodsmentioning
confidence: 99%
“…1b ) an epoxide and an important irreversible inhibitor against general cysteine proteases and displayed a significant outcome on growth, adherence and viability of parasite trophozoites. 12 A representative of benzoxaboroles, AN3661 ( Fig. 1c ), has been found to markedly reduce the FP2 transcripts in malarial parasites.…”
Section: Introductionmentioning
confidence: 95%